EDITORIAL (2019)
Santo Tomás University, Tunja Sectional, presents the magazine Principia Iuris No. 30, in which topics of vital importance are developed for the legal progress conceived from the social projection, the axiological and epistemological bases in the solution of the different disciplinary and interdisciplinary research problems. The investigations of this edition are the development of topics that include a great content of social and legal issues, both in a national and international context. On this occasion, the Magazine Principia Iuris, 30 Serial, presents its research development in three sections: The first section, studies THE TEXTUAL AND CONTEXTUAL RELATIONSHIP OF HUMAN RIGHTS IN THE FIELD OF THE PROTECTION OF BOYS, GIRLS AND TEENAGERS; that is oriented towards a concrete vision of the teleological scope of social inclusion in Colombia. The second, addresses, ORDINARY AND TRANSITIONAL JUSTICE; an approximation adjusted to the general principles of Law. And finally, PUBLIC POLICIES, GLOBALIZATION AND ADMINISTRATIVE LAW IN COLOMBIA; seeking to establish parameters in the current model of Justice Administration. The effort, permanent and inexhaustible of the jurists and participants of this edition, we highlight, and with its greatness, all the science of law.